Implementation of and to and in data security and privacy of the WhatsApp social media application - Tendri Harnovik; T.M.A Azis Alfarisy; Widia Hutapea; Supina Batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research explores the implementation of